In Vitro andIn Vivo Experimental Model-based Approaches for Investigating Anti-inflammatory Properties of Coumarins - Gagliotti Vigil de Mello, Silvana V.; Frode, Tania Silvia (Current Medicinal Chemistry, 2018)
Background: Coumarins are polyphenolic compounds that are often used to treat inflammatory conditions in complementary and alternative medicine. Objective: In this study, we reviewed reports of in vivo and in vitro experimental modelbased approaches investigating the potential anti-inflammatory properties of coumarins. Methods: A literature search of PUBMED, MEDLINE, Web of Science, and Scopus was performed covering the period from 1 January 2005 to 31 December 2015. The keywords used to search were ‘anti-inflammatory’ and ‘coumarin’ and ‘in vivo’ or ‘in vitro’. This search identified 425 article titles. Results: Of the 425 article titles, 127 full-text articles were reviewed, and 69 of them were included in the analysis. Most of the studies (81.2%) used in vitro assays. The studies focused on cytokines such as tumour necrosis factor (TNF), interleukin (IL)-6, and IL-1-β (55.1%), as well as oedema (46.5%), nitric oxide (NO, 23.2%), oxidative stress (21.7%), inflammatory cells (21.7%), nuclear factor (NF)-ΚB (24.6%), mitogen-activated protein kinase (MAPK, 13%), myeloperoxidase (MPO, (15.9%), cyclooxygenase (COX)-2 (14.5%), prostaglandin E2 (PGE2, 8.7%), 5-lipoxygenase (LOX, 4.3%), and adhesion molecules (7.2%). Coumarins inhibited all these parameters except for IL-10, nuclear factor erythroid 2 (NFE2)-related-factor 2 (Nrf2), and regulatory T cell (Treg) differentiation. Conclusion: In vitro methods were the most commonly used to study the antiinflammatory effects of coumarins. The results showed that coumarins exerted antiinflammatory and antioxidant activities by inhibiting NF-ΚB, nuclear factor of activated T cells (NFAT), retinoic acid-related orphan receptor γΤ (RORγΤ), and MAPK and increasing Nrf2 activation. These results suggest that coumarins could be important candidates for the development of novel anti-inflammatory therapeutic drugs.
Keywords: in vivo